A Compact oxygen concentrator for premature infants: Integrating portability and performance in the third-generation prototype - Cornelia Christiani Vianney; Raldi Artono Koestoer; Yudan Whulanza; Imansyah Ibnu Hakim (BKS-TM Indonesia, 2025)
Oxygen concentrators are vital devices in medical oxygen therapy. It provides supplemental oxygen, extracted from the environmental air, to patients suffering from hypoxemia or other clinical conditions characterized by low blood oxygen saturation. The need for oxygen therapy extends across various patient populations, including adults, children, and neonates, especially premature infants. However, commercially available concentrators are usually designed for adults, making them unsuitable for premature infants whose delicate, underdeveloped organs can be harmed by high oxygen levels. Meanwhile, field observations from the Indonesian Incubator Team indicate frequent demand for supplemental oxygen following hospital discharge. To meet the urgent need for a suitable device, especially for premature infants discharged from hospitals, this study describes the design and development of a compact, portable, and neonatal-specific oxygen concentrator. A reverse engineering approach was adopted through a three-phase prototyping process. The first prototype verified the feasibility of the pressure swing adsorption (PSA) principle as the main process of the oxygen concentrator. The second prototype integrated a complete system to evaluate performance by measuring flow rate and oxygen concentration and adjusting components to achieve optimal results. The final, third prototype refined the design to improve compactness and portability. The device achieved an oxygen concentration of about 40% oxygen purity with a steady flow rate of 2 L/min. This developed oxygen concentrator presents a significant step forward in neonatal care, providing a tailored and accessible solution that can support widespread use in home-based infant healthcare programs.